161k views
2 votes
PLEASE HELP!!!!!!!!!!!!

PLEASE HELP!!!!!!!!!!!!-example-1

1 Answer

6 votes

Answers:

a = 3

x intercept = -2

===========================================================

Step-by-step explanation:

f(x) is the original function given. Let g(x) be the inverse of f(x).

To find the inverse, we first replace f(x) with y to get

y = (1/3)x-2

Afterward, we swap x and y to get

x = (1/3)y-2

From here, we must isolate or solve for y. To do so, add 2 to both sides and then multiply both sides by 3

x = (1/3)y-2

x+2 = (1/3)y

3(x+2) = y

y = 3(x+2)

g(x) = 3(x+2)

This explains where the x+2 comes from in the a(x+2) expression

The value of 'a' is therefore a = 3

------------

To find the x intercept of the inverse, we replace g(x) with 0 and solve for x

g(x) = 3(x+2)

0 = 3(x+2)

0/3 = x+2

0 = x+2

x+2 = 0

x = 0-2

x = -2

The x intercept is x = -2. Plugging this x value into g(x) leads to g(x) = 0.

The g(x) graph crosses the x axis at x = -2.

User NoDachi
by
6.2k points